Total Physical Response Method in Understanding English Vocabulary in Kranji Village - Sumilis (JELP Journal of English Language and Pedagogy, 2024)
The purpose of this study is to find out the obstacles experienced by students of the bimbel program in Kranji village, Lamongan Regency regarding vocabulary understanding. This research is a case study with linguistic analysis approach. The data in this study were obtained through questionnaire method containing 7 statements about pronunciation. The statements are about learning good pronunciation, practicing speech activities in daily vocabulary use. Understanding on pronunciation in the teaching and learning process in class, correcting pronunciation mistakes in class, using local or regional accent when teaching English, using local or regional accent when speaking in English, problems in pronouncing certain sounds caused by local accent or regional accent. The results showed that 10 students gave different responses. Teachers should also give examples in giving directions, so that students can respond and understand English lessons well as the objectives in learning.